Optimization of Tannin Removal from Marigold Flowers by Water Extraction as Pretreatment for Lutein Recovery - Mukmin Sapto Pamungkas; Sherly Maharani Puspita Sari; Edia Rahayuningsih (Eksergi, 2026)
Lutein extraction from marigold flowers (Tagetes erecta L.) with organic solvents is related to the presence of tannin-type phenolic compounds, capable of affecting the quality of food products. Therefore, this study aimed to evaluate the potential of water pretreatment to selectively extract tannins before lutein extraction. The experiment was conducted using water as a solvent for extraction due to its high and low selectivity for phenolic compounds and carotenoids, respectively. The extraction of tannins was investigated with respect to stirring speed, extraction time, and water-to-solid ratio using Response Surface Methodology (RSM) design of central composite. Tannins were extracted in a 1 L beaker at ambient temperature, and total phenolic content (TPC) was measured by spectrophotometry using the Folin-Ciocalteu method. The results showed that the quadratic model predicted the optimum extraction conditions as a stirring speed of 579 rpm, extraction time of 4.6 h, and water–solids ratio of 25 mL g−1 dry weight. At these extraction conditions, the process achieved a predicted TPC of 376.76 mg g−1 dry weight with 75.37% removal of tannin. Additionally, visible spectrophotometry confirmed the selectivity of the water-based extraction, as only 1.7% of the initial carotenoid content was present in the water extract.